Shared passion Anne and Michel Vandenkerckhove, a collection of the 21st century - Claes, Didier; Vandenkerckhove, Michel 19XX-; Bouttiaux-Ndiaye, Anne-Marie (Mercatorfonds, 2023)
This book documents and celebrates the patience and perseverance of, and the friendship between, the Belgian collector Michel Vandenkerckhove and the Belgian art dealer and gallerist Didier Claes, and the exceptional African art collection that is the result of their collaboration. Alongside stunning black and white images of masks, figures, and utilitarian objects from numerous sites across the African continent and from a variety of time periods, essays by art historian Bruno Claessens expound on the most interesting aspects of this collection. Four separate topics are examined in depth: the abstract guardian figures of the Kota, the power statues of the Kongo, the enigmatic art of the Lega, and the much-loved ikhoko pendants of the Pende. An innovative graphic design, featuring photography by Hughes Dubois, shines a light on this extraordinary collection, available to the public for the first time through this publication
Keywords: Vandenkerckhove, Michel -- 19XX-; Vandenkerckhove, Anne -- 19XX-; Kunsthandwerk; Kunst; Subsaharisches Afrika; Vandenkerckhove, Anne / Art collections / Catalogs; Vandenkerckhove, Michel / Art collections / Catalogs; Art, African / Private collections / Catalogs; Art africain / Collections privées / Catalogues; Bildband